2011
DOI: 10.1111/j.2042-7158.2011.01367.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ganoderma lucidum polysaccharides on IEC-6 cell proliferation, migration and morphology of differentiation benefiting intestinal epithelium healing in vitro

Abstract: These results suggest the potential usefulness of Gl-PS to cure intestinal disorders characterized by injury and ineffective repair of the intestinal mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…These beneficial features are similar to those with hydrophilic bandage soft contact lenses whose high oxygen permeability is thought to be able to promote epithelial migration and enhance epithelial stromal adhesion [ 29 ]. When corneal epithelial cells were co-cultured with polysaccharide, the rate of cell migration was significantly increased, consistent with previous reports [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…These beneficial features are similar to those with hydrophilic bandage soft contact lenses whose high oxygen permeability is thought to be able to promote epithelial migration and enhance epithelial stromal adhesion [ 29 ]. When corneal epithelial cells were co-cultured with polysaccharide, the rate of cell migration was significantly increased, consistent with previous reports [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…The water-soluble polysaccharide fractions of G. lucidum have been reported to have healing effects especially on ulcer lesions [32, 33]. Elsewhere, Sun et al [34] reported that G. lucidum polysaccharides showed healing effects on intestinal epithelium using a nontransformed small-intestinal epithelial cell line, IEC-6 cells. Despite all the beneficial wound healing effects of G. lucidum , little attention has been paid to its effects on wounds associated to diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Chrysanthemi flos compounds inhibit NO, PGE-2, TNF- α , and IL-1 β production, as well as iNOS and COX-2 expression in LPS-induced macrophages [ 60 ]. Ganoderma lucidum showed positive effects on intestinal epithelium healing [ 61 ] and refractory diabetic wounds [ 62 ] and was found to decrease NO, PGE-2, and proinflammatory cytokine production, including IL-1 β , TNF- α and NF- κ B in microglia [ 63 ]. Menthae haplocalycis herba in TCM theory is used for mouth sores, exanthema, and itching [ 24 – 26 ].…”
Section: Herbal Combinationsmentioning
confidence: 99%